INTRODUCTION TO THE JJAS SPECIAL ISSUE “CELEBRATING THE COUNTRY'S CENTENARY”: THE DEVELOPMENT OF SCIENCES AND TECHNOLOGY OF AGRICULTURE, FOOD, AND NUTRITION IN JORDAN - AHMAD, MOUSA NUMAN (Jordan Journal of Agricultural Sciences, 2021)
This JJAS special issue on “The Development of Sciences and Technology of Agriculture, Food, and Nutrition in Jordan” has been announced soon after the declaration of the official day of the centenary of the founding of the Jordanian state on the 11th of April 2021 (Ahmad, 2021). The issue comprises 13 invited review articles that describe the advancement in basic and applied scientific research in the fields of agriculture, food, and nutrition in a hundred years of the country’s establishment. The development in science and technology of these fields has emerged as a powerful paradigm for Jordan’s next generation of economics, food security, and human health (JIC, 2018).